Optimalisasi Metode Storytelling dalam Meningkatkan Literasi Anak tentang Area Privasi Tubuh sebagai Upaya Pencegahan Kekerasan Seksual - Kiki Asrifa Dinen; Yuli Zuhkrina; Meylissa; Dian Rahayu; Ully Fitria; Fajar Hariadi (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
Sexual violence against children is a global problem that has serious impacts on their physical, psychological, and social development. One preventative measure is to increase children's literacy regarding bodily privacy from an early age. This community service activity aims to increase children's knowledge about bodily privacy through storytelling. The activity was conducted in Jeumpeut Ajun Village, Darul Imarah District, Aceh Besar Regency, targeting elementary school-aged children. The methods used were educational counseling using storytelling media, illustrated posters, interactive discussions, and evaluation using a pre-test and post-test design. A total of 15 children participated in this activity. The analysis showed that the average knowledge score of the children before the intervention was 49.33 and increased to 84.67 after the intervention. The paired sample t-test showed a p-value of 0.000 (p<0.05), indicating a significant difference between the pre-test and post-test scores. These results indicate that the storytelling method is effective in increasing children's understanding of bodily privacy as a preventative measure for child sexual violence.